2002
DOI: 10.1074/jbc.m200545200
|View full text |Cite
|
Sign up to set email alerts
|

Liganded Androgen Receptor Interaction with β-Catenin

Abstract: A yeast two-hybrid assay was employed to identify androgen receptor (AR) protein partners in gonadotropin-releasing hormone neuronal cells. By using an AR deletion construct (AR-(⌬371-485)) as a bait, ␤-catenin was identified as an AR-interacting protein from a gonadotropin-releasing hormone neuronal cell library. Immunolocalization of co-transfected AR and FLAG-␤-catenin demonstrated that FLAG-␤-catenin was predominantly cytoplasmic in the absence of androgen. In the presence of 5␣-dihydrotestosterone, FLAG-␤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
3
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(66 citation statements)
references
References 58 publications
7
53
3
3
Order By: Relevance
“…It is not surprising that ␤-catenin and SF1 synergistically activate the MISRII promoter. ␤-Catenin interacts with a number of factors to exert its biological effects, the nuclear hormone receptor RXR and androgen receptors among them (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…It is not surprising that ␤-catenin and SF1 synergistically activate the MISRII promoter. ␤-Catenin interacts with a number of factors to exert its biological effects, the nuclear hormone receptor RXR and androgen receptors among them (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…For example, PTEN regulates, by way of altered GSK3b function, the localization of b-catenin, its transcriptional effector, T-cell factor (Tcf) (Persad et al, 2001b;Sharma et al, 2002) and its target cell cycle regulator, cyclin D1 (Radu et al, 2003). Loss of PTEN may, therefore, result in increased nuclear localization of AR/b-catenin complexes (Mulholland et al, 2002;Pawlowski et al, 2002), potentially leading to alteration of cell cycle events or ligand specificity of AR. A logical extrapolation is that PTEN loss may promote AR gain-of-function by modulating other known AR coregulators including ARA70 (Yeh and Chang, 1996) and ARA54 (Kang et al, 1999), thereby permitting responsiveness to low androgen levels or nonandrogen ligands.…”
Section: Loss Of Pten Provides a Gain-of-function 'Environment' For Armentioning
confidence: 99%
“…b-Catenin can enhance cell proliferation (Mulholland et al, 2003;Masiello et al, 2004), production of PSA and increase AR responsiveness to nonandrogen ligands, including estrogens (Truica et al, 2000;Pawlowski et al, 2002;Song et al, 2003b;Mulholland et al, 2003;. Mice with prostate-specific deletion of the b-catenin regulatory domain (Dexon 3) are reported to develop metaplasia and, in some instances, neoplastic transformation (Bierie et al, 2003;Gounari et al, 2002).…”
Section: Pi3k/akt and Ar: Critical Regulators Of Progression To Ai Prcamentioning
confidence: 99%
“…b-Catenin has also been described as a liganddependent coactivator of the AR (Truica et al, 2000;Mulholland et al, 2002;Pawlowski et al, 2002;Yang et al, 2002). Previously, we have shown that translocating AR can provide a means of nuclear entry and accumulation of b-catenin (Mulholland et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we have shown that translocating AR can provide a means of nuclear entry and accumulation of b-catenin (Mulholland et al, 2002). This mode of b-catenin trafficking has also been shown to hold true in neuronal cells (Pawlowski et al, 2002). Cotrafficking of AR and b-catenin to the nucleus likely has important implications both for AR and Wnt signaling.…”
Section: Introductionmentioning
confidence: 99%